Facilitators and barriers of physical activity, sedentariness and exercise adoption among healthcare professionals in Lagos State, Nigeria – A qualitative review - Blossom Adaeze Maduafokwa; Mobolanle Balogun; Kamaldeen Sunkanmi Abdulraheem (PLoS ONE, 2026)
Physical inactivity is a major global public health concern, identified by the World Health Organization as the fourth leading cause of mortality worldwide and associated with an estimated 3.2 million deaths annually. Healthcare professionals (HCPs) serve as frontline advocates for health promotion and disease prevention, yet many struggle to maintain adequate levels of physical activity themselves, which not only compromises their health but also diminishes their capacity to counsel patients effectively. This qualitative study explored the facilitators and barriers of physical inactivity, sedentariness, and exercise adoption among healthcare professionals in Lagos State, Nigeria, using the Social Ecological Model (SEM) to examine influences at individual, interpersonal, organizational, community, and policy levels. Data were collected through six focus group discussions with healthcare professionals, four in-depth interviews with family members of HCPs, and five key informant interviews with healthcare facility heads and policy makers in urban planning in Lagos State. Findings revealed that time constraints, heavy workloads, inadequate infrastructure, safety concerns, and cultural norms were major barriers to physical activity, while facilitators included peer support, leadership engagement, self-efficacy, and incentives such as free gym access. Organizational strategies such as provision of onsite gyms at healthcare facilities, scheduled breaks, and promotion of a workplace fitness culture were identified as critical enablers. The study highlights the urgent need for comprehensive, multi-level interventions to address barriers and strengthen facilitators of physical activity among healthcare professionals. Addressing these gaps is essential not only for improving their health but also for enhancing their role as credible advocates of active lifestyles.